Degradation of Remazol Yellow FG by Sonolysis and Photolysis with TiO2/Active Carbon Rice Husk (TiO2/AC) Catalyst and Analysis Using Spectrophotometer UV-Vis - Safni; Putri, Anggi Nabila; Deswati, Deswati; Zilfa, Zilfa (Departemen Kimia Universitas Andalas, 2024)
Remazol Yellow FG is one of the dyes that are often used in the textile industry because it is accessible and reasonably priced. The non-biodegradable dyes produce waste and inhibit sunlight from passing through the water. In this study, we performed Fourier Transform Infrared (FTIR) to characterise the activated carbon of rice husk and TiO2/activated carbon rice husk (TiO2/AC) using Diffuse Reflectance Spectroscopy UV-Vis (DRS UV-Vis). Remazol Yellow FG was degraded by using sonolysis and photolysis under UV ray (λ = 254 and 365 nm) and visible ray. We performed the experiments using a variety of variables which consist of catalyst dosage (10–50 mg), contact time (1–6 hours), catalyst type (AC, TiO2 and TiO2/AC), lamp type (365 nm, 254 nm and visible lamp) and initial Remazol Yellow FG concentration (10–30 mg/L) to determine the degradation percentage. We found that the addition of TiO2/AC catalyst increased the degradation percentage of Remazol Yellow FG from 6,86% to 52,62% using sonolysis and 8,34% to 95,02% using photolysis. Hence, we concluded that TiO2/AC catalyst from rice husk could be an effective catalyst for the Remazol Yellow FG degradation.